2020
DOI: 10.1186/s12872-020-01732-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cigarette smoking on biventricular systolic function independent of respiratory function: a cross-sectional study

Abstract: Background Cigarette smoking harms nearly every organ, including the heart and lungs. A comprehensive assessment of both cardiac and respiratory function is necessary for evaluating the direct effects of tobacco on the heart. However, few previous studies examining the effects of cigarette smoking on cardiac function included an assessment of lung function. This cross-sectional study investigated the influence of cigarette smoking on cardiac function, independent of respiratory function. Methods We retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
(57 reference statements)
0
3
0
1
Order By: Relevance
“…Cigarette smoking is strongly associated with cardiac remodeling and dysfunction (4)(5)(6)(7)(8)(9)(10)(11). Early clinical studies of novel tobacco products have shown promising reductions in cardiovascular diseases when compared to cigarette smoking (23,26,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cigarette smoking is strongly associated with cardiac remodeling and dysfunction (4)(5)(6)(7)(8)(9)(10)(11). Early clinical studies of novel tobacco products have shown promising reductions in cardiovascular diseases when compared to cigarette smoking (23,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac remodeling is concerning due to its propensity to decompensate toward cardiac dysfunction and disease states including myocardial infarction and heart failure (HF) (2,3). Cardiac remodeling, cardiac dysfunction, and HF are significantly associated with both current and former cigarette smoking, as well as second-hand smoke exposure (4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…None of them used drugs or had a known disease, pathological state, or clinical condition that could affect the results. Because of the known negative effects of smoking on cardiac function, all subjects were non-smokers [ 9 ]. The present retrospective cohort study is part of the Motion Analysis of the heart and Great vessels bY three-dimensionAl speckle-tRacking echocardiography in Healthy subjects (MAGYAR-Healthy) Study, which has been organized at the University of Szeged partly for the purpose of examining physiologic correlations (‘Magyar’ means ‘Hungarian’ in the Hungarian language).…”
Section: Methodsmentioning
confidence: 99%
“…Ретроспективне дослідження, проведене Yusuke Watanabe at al. [10], встановило, що висока експозиція тютюном (≥20 пачко-років) мала прямий кореляційний зв'язок зі зниженою бівентрикулярною систолічною функцією серця, незалежно від функції дихання. Ці висновки підтверджують, що куріння може призвести до розвитку міокардіального ремоделювання, значної серцевої дисфункції та серцевої недостатності внаслідок прямого безперервного дозозалежного впливу сигаретного диму [10].…”
unclassified